Limb salvage in a lower extremity with no venous circulation: free muscle sparring latissimus dorsi cross-leg flap - a case report - Rendón-Medina, Marco Aurelio; Rendón-Pimentel, Marco Antonio; Vargas-Rocha, Manuel; Hanson-Viana, Erik; Montes-Munguia, Mariana; Herndandez-Ordoñez, Rubén (International Journal of Research in Medical Sciences, 2024)
<div class="min-h-[20px] text-message flex w-full flex-col items-end gap-2 break-words [.text-message+&]:mt-5 overflow-x-auto whitespace-normal" dir="auto" data-message-author-role="assistant" data-message-id="9af4e4c2-9596-408b-83d8-ea0bea68e24a"> Lower extremity trauma is prevalent in Mexico, with tibial fractures in about 15% of cases and wounds in 37%. Reconstruction, particularly with severe crush injuries, is challenging due to the risk of complete devascularization. The Gustilo-Anderson classification is essential for evaluating injury severity and vascular risks, and advanced planning is critical for severe cases. A 49-year-old male with systemic hypertension sustained blunt and crush trauma to the left leg. Initially managed with external fixation without fracture reduction, the patient was later referred to our centre. Angio tomography revealed a severe Gustilo-Anderson IIIB tibial fracture with diminished vascular flow and no detectable veins. We performed two interventions, ultimately utilizing a free latissimus dorsi flap to achieve successful coverage. In complex cases with limited recipient vessels, comprehensive diagnostic methods such as angiography and ultrasound are crucial. These tools provide vital information for precise surgical planning and improve patient outcomes.